(untitled) (Research, Society and Development, 2023)
Objective: To describe the consumption profile of antidepressants and benzodiazepines in a Basic Health Unit in the Federal District before and during the COVID-19 Pandemic in order to observe the impact on the mental health of the population that uses this service. Methodology: This is a cross-sectional, descriptive study, with a retrospective analysis carried out by collecting data on the dispensing of antidepressants and benzodiazepines from a pharmacy in a Basic Health Unit Federal District. These data were collected from the psychotropic drug record book for the years 2019 to 2022. Results: An increase in the dispensation of antidepressants and benzodiazepines was observed in the years 2020, 2021 and 2022, pandemic years, when compared to year 2019.Conclusion: This study made it possible to visualize an increase in the consumption of some psychotropic drugs during the period of the COVID-19 pandemic, as a probable consequence of the increase in cases of psychological distress in the population served by a Basic Health Unit in the Federal District.